Fieldworker and the field: problems and challenges in sociological investigation - Srinivas,M.N. (ed.); Shah,A.M. (ed.); Ramaswamy,E.A. (ed.) (Delhi, 1979)
Long considered to be the hallmark of social and cultural anthropology, intensive fieldwork has gained widespread acceptance in the social sciences. The use of this method to study a wide array of problems from tribes and villages to hospitals and trade unions poses practical, methodological and moral problems scarcely anticipated when it was confined to the study of simple societies. Is role assumption by the fieldworker necessary and feasible in a complex society? Can the fieldworker avoid involvement with the people and yet collect reliable data? Can entire communities be studied in accordance with the old maxim? If not, what choices do fieldworkers have? Can they keep aside their personal biases? How should the fieldworker handle moral problems? Should he stand by his 'progressive' views in a 'traditional' society, or choose a more expedient course? The eighteen papers in this collection portraying actual field experiences-fifteen in India and three outside India-focus on these problems. They capture the intense excitement of fieldwork and highlight the fact that social knowledge is different from natural knowledge. Fieldwork involves not merely the intellect but the entire psyche of the researcher, and his data have no existence independent of him.
Keywords: Sociology